Quelques problèmes de traduction du registre populaire français en langue hongroise - Gulyás, Adrienn (Verbum – Analecta Neolatina, 2006)
Difficulties of translating socially marked speech from French into Hungarian are analyzed. The corpus is based on a French crime fiction by Fred Vargas, translated into Hungarian by myself. Firstly, I deal with the strategies and techniques of social marking in the French version. Then, I turn to the Hungarian translation and see whether the socially marked character of the original text could be rendered and, if yes, what kind of markers were used. Differences seem to arise from the fact that popular French, as a register, does not have a perfect equivalent in Hungarian. This "deficiency" becomes most striking in the domain of syntax. While the French author uses mainly syntactic devices to mark popular speech, the translationmust rely on phonetic and lexical markers, given that syntactic differences between standard Hungarian and its non-standard varieties are almost null. Also, while markers are clearly popular throughout the French version, the Hungarian translation renders either a dialectically marked speech, for non-Parisian popular French speakers, or a kind of urban slang, for Parisian popular French speakers.